2003
DOI: 10.1103/physreva.67.012501
|View full text |Cite
|
Sign up to set email alerts
|

Criticality of the electron-nucleus cusp condition to local effective potential-energy theories

Abstract: Local(multiplicative) effective potential energy theories of electronic structure comprise the transformation of the Schrödinger equation for interacting fermi systems to model noninteracting fermi or bose systems whereby the equivalent density and energy are obtained. By employing the integrated form of the Kato electron-nucleus cusp condition, we prove that the effective electron -interaction potential energy of these model fermions or bosons is finite at a nucleus. The proof is general and valid for arbitra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The corresponding electron-interaction potential energy v ee (r) representative of these correlations as determined by the work done in the force of these fields is then symmetric about this point as also dictated by the symmetry of the molecule. The potential energy v ee (r) is also finite at each nucleus, as must be the case [23].…”
Section: B Fermi-coulomb Fermi and Coulomb Holesmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding electron-interaction potential energy v ee (r) representative of these correlations as determined by the work done in the force of these fields is then symmetric about this point as also dictated by the symmetry of the molecule. The potential energy v ee (r) is also finite at each nucleus, as must be the case [23].…”
Section: B Fermi-coulomb Fermi and Coulomb Holesmentioning
confidence: 99%
“…Furthermore, it is shown that this finiteness is a direct consequence of the satisfaction of the electron-nucleus cusp condition by the Schrodinger wave function. (As a consequence, for example, this potential energy is singular at each nucleus when determined either from Gaussian geminal [23] or configuration interaction [25] wave functions.) Hence, in order to obtain v c (0, z), we have employed our calculated results in regions other than near the nucleus, and smoothed the curve through each nucleus.…”
Section: B Fermi-coulomb Fermi and Coulomb Holesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the RPA gives poor description of the short-range correlations of the electrons, especially for g(r) as r → 0. In fact, the results for g ↑↓ (r) in the RPA violate the following cusp condition: [14,17,24,25,26,27] ∂g ↑↓ (r) ∂r…”
Section: Introductionmentioning
confidence: 99%
“…Standing on the middle rung of Jacob's ladder, we can-not see the next rung. With more research on physical models and also constraint satisfaction [19][20][21][22][23][24][25][26][27][28], the nature of exchange-correlation functional will be gradually uncovered. However, this research can hardly help design a better exchange-correlation functional, and we believe that this is because these models or constraints can-not suggest the form of exchange-correlation functional directly.…”
Section: Introductionmentioning
confidence: 99%